Analysis of Students' Communication Politeness Capabilities Towards Lecturers in an Academic Environment: Case Study at FKIP Universitas Perjuangan Tasikmalaya - Jumadil Saputra; Setyo Yohandoko; Volodymyr Rusyn (Research Collaboration Community (RCC), 2024)
This research investigates students' polite communication skills towards lecturers in an academic environment. Data was collected through observations and interviews with students from the Indonesian Language and Literature Education Study Program at FKIP Universitas Perjuangan Tasikmalaya. The main finding is that most students tend to use less polite language in communication with lecturers, including the use of slang, non-compliance with communication ethics, and lack of use of polite words such as